Determinant Analysis of Going Concern Audit Opinion - Kadek Indah Kusuma Dewi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aims to examine and analyze the determinants of going concern audit opinion (an empirical study of consumer good industry sub-sector manufacturing companies on the IDX in 2017-2021). The population in this study is that there are 37 Consumer Good Industry Companies listed on the Indonesia Stock Exchange issued financial reports for 2017-2021. This research approach is positivist by testing the research variables. Also, purposive sampling was chosen to determine the unit of analysis. Data analysis used logistic regression with the help of the SPSS software program. SPSS output shows the result that going concern audit opinion is influenced by debt ratio, company size, audit lag. Meanwhile, audit quality and financial distress do not affect the going concern audit opinion given by the auditor.